2017
DOI: 10.1007/s11255-017-1654-3
|View full text |Cite
|
Sign up to set email alerts
|

High glucose stimulates cell proliferation and Collagen IV production in rat mesangial cells through inhibiting AMPK-KATP signaling

Abstract: Taken together, activating AMPK-K signaling may protect against HG-induced mesangial cell proliferation and Collagen IV production, and, thereby, provides new insights into the molecular mechanisms underlying early diabetic nephropathy (DN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…We validated several candidates from this subset and confirmed that many of the downregulated genes are well-known pro-proliferative genes and the upregulated ones are antiproliferative genes (Figure ). There are a number of studies showing the involvement of glucose in the context of cell proliferation, and we observed that TCF19 is overexpressed upon glucose stimulation . Our data suggest that TCF19 regulates the optimum uptake levels of glucose to maintain a sustainable concentration of glucose in the hepatic cell.…”
Section: Discussionsupporting
confidence: 62%
“…We validated several candidates from this subset and confirmed that many of the downregulated genes are well-known pro-proliferative genes and the upregulated ones are antiproliferative genes (Figure ). There are a number of studies showing the involvement of glucose in the context of cell proliferation, and we observed that TCF19 is overexpressed upon glucose stimulation . Our data suggest that TCF19 regulates the optimum uptake levels of glucose to maintain a sustainable concentration of glucose in the hepatic cell.…”
Section: Discussionsupporting
confidence: 62%
“…In consistent with these reports, we observed impaired AMPK phosphorylation in diabetic renal tissue as well as in tubular cells incubated with high glucose levels. The impaired AMPK activity in renal tissue positively correlates with mesangial matrix deposition and inefficient tubular reabsorption (Wei et al, 2020; Zhang et al, 2017). Melatonin treatment in STZ‐induced diabetic rats and high‐glucose‐exposed NRK‐52E cells improved AMPK phosphorylation, demonstrating the positive modulatory effect of melatonin on AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…This process inhibits AMPK activation which causes renal hypertrophy and fibrosis in hyperglycemic and hyperlipidemic conditions by regulating several pathways, and has been seen in both in vitro and in vivo experiments. In contrast, activation of AMPK suppressed both renal fibrosis and improved renal function in both in vitro and in vivo experiments [15, 44]. Therefore, AMPK could provide a potential approach to alleviate diabetic renal damage [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TGF-β1, a predominant pathogenic factor, regulates glomerular and tubulointerstitial fibrosis by the phosphorylation and activation of Smad2 and Smad3 as well as the canonical signaling pathway [14]. It is also known that AMP-activated kinase protein (AMPK) acts as a cellular energy homeostasis mediator and contributes to mesangial cell proliferation and fibrosis production [15].…”
Section: Introductionmentioning
confidence: 99%